Direction in Curriculum and Mathematics Learning Model in Inclusive School: A Systematic Literature Review - Junarti; Ima Isnaini Taufiqur Rohmah; Dwi Erna Novianti (Proceeding International Conference on Digital Education and Social Science, 2024)
This study aimed to explore the direction in curriculum and mathematics learning model which were implemented in inclusive school. This study used Systematic Literature Review by selecting scientific articles published in 1990 – 2024 and categorizing them based on the curriculum and mathematics learning model. This study implemented PRISMA method. The data was collected using the official sites of Science Direct, Sinta, ResearchGate, and Garuda. The data was filtered using keywords of curriculum and mathematics learning model in inclusive education. Based on 21 national articles and 7 international articles which discussed the curriculum of inclusive school, there were 5 types of curriculum, namely 1) the Specific Learning Disabilities (SLD) curriculum that was equaled with differentiated regular class curriculum; 2) the curriculum was equaled with general children’ curriculum; 3) Merdeka Curriculum; 4) modified curriculum; 5) National curriculum which was integrated with spiritual and akhlaqul kharimah education. In addition, the modes used in mathematics learning which were stated in 17 articles lead to 7 learning models, namely 1) differentiated learning model; 2) modified learning model with direct instruction and/or curricular design; 3) thematic approach; 4) scientific approach; 5) providing additional explanation as reinforcement; 6) joining regular students; 7) empirical approach and theoretical perspective. Based on 17 articles, there were 6 articles which discussed about differentiated learning model. Moreover, 11 articles discussed another learning models. It could be concluded that the direction in curriculum of inclusive school was dominant in implementing modified curriculum and differentiated learning model.